MANAJEMEN STRATEGI PAIKEM (PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN) DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PAIDI KELAS IX SEKOLAH MENENGAH PERTAMANEGERI 10 KABUPATEN TANJUNG JABUNG BARAT PROVINSI JAMBI - Ferdi Dwi Novanto; Lukman Hakim; Najmul Hayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of classroom management using the PAIKEM strategy (Active, Innovative, Creative, Effective, and Enjoyable Learning) in Islamic Religious Education (PAI) learning and its impact on students’ learning interest and achievement at SMP Negeri 10 Tanjung Jabung Barat. This research employed a qualitative approach with data collection techniques including in-depth interviews, participatory observation, and document analysis. The findings indicate that classroom management based on the PAIKEM strategy was implemented systematically through the stages of planning, organizing, actuating, and controlling. This strategy successfully created an active, interactive, and meaningful learning environment and positioned students as active participants in the learning process. The implementation of PAIKEM had a positive impact on increasing students’ learning interest, classroom participation, and learning achievement in cognitive, affective, and psychomotor aspects. Therefore, classroom management using the PAIKEM strategy is proven to be effective in improving the quality of Islamic Religious Education learning and supporting students’ character development. Keywords: classroom management, PAIKEM strategy, Islamic Religious Education, learning interest, learning achievement.